Relationship Between Gender and 1-Year Mortality in ANCA-Associated Vasculitis Patients: A Single-Center Retrospective Analysis and Meta-Analysis - Zhu, Qing; Li, Fen; Xie, Xi; Chen, Bilin; Yu, Qianwen; Wei, Yusong; Ge, Yan (Frontiers in Medicine, 2022)
Abstract Objective: The relationship between gender and short-term prognosis of anti-neutrophil cytoplasmic antibody (ANCA) associated vasculitis (AAV) patient is unclear, single-center retrospective analysis and meta-analysis were conducted to determine the relationship. Methods: Initially treated AAV patients were retrospectively enrolled. Data of clinical manifestation, laboratory indicators, Birmingham Vasculitis Activity Score (BVAS), therapeutic treatment and patients' situation within 1 year were recorded. Basic characteristics between males and females were compared firstly. Secondly, the risk factors associated with 1-year mortality rate of AAV patients were evaluated. Finally, meta-analysis was performed to explore the effect of gender on 1-year mortality in AAV patients. Results: 84 AAV patients were included, including 33 females and 51 males. 14 people died (12 males and 2 females) and 70 survived in 1 year. Statistical differences were noted in the age of onset, the course of the disease, WBC, HB, N, ESR, CRP, BUN, ALT and ALB, BVAS and 1-year mortality rate between males and females. Male, elevated Scr, NLR, PLT and RDW-CV were associated with poor prognosis of AAV patients (P<0.05). Meta-analysis verified male was an independent risk factor for 1-year mortality of AAV patients (OR=1.54). Conclusion: Significant sex specific differences were found in AAV patients. Male contributed to 1.54-fold of 1-year mortality risk in AAV patients by meta-analysis. More attention should be paid to the mortality risk of male AAV patients in early stage.